An investigation into the crude oil price pass-through to the macroeconomic activities of Malaysia - Alom, Fardous (2015)
This study examines the pass-through of crude oil prices into economic activities of Malaysia including industrial production index (IP), consumer price index (CPI), real effective exchange rate (REER), interest rate (IR) and stock price index (SPI) within the framework of hidden cointegration technique over the quarterly data ranging from 1987 to 2013. The estimated results suggest that positive and negative changes of IP, CPI, REER, IR and SPI do not maintain a long-run association with positive as well as negative changes of real crude oil prices excepting negative changes in IP. Negative changes in IP are found to be cointegrated with the positive changes of crude oil prices. Although Malaysia is considered as one of the net oil exporter country, the higher oil prices still dampen the industrial production in the long run; the findings is consistent with Ali Ahmed and Wadud (2011).